A deeper understanding of the syntactic behavior of phrasal verbs - Al-Shunnag, Mohammad Awad; Ahmed, Wasan Khalid; Alwreika, Emad Abedalaziz; Alhammaideh, Abdullah; Alqaryouti, Marwan Harb (International Journal of Innovative Research and Scientific Studies, 2025)
The present paper examines the syntactic features of phrasal verbs among EFL students. The main objectives of conducting this study are to recognize those syntactic features associated with language acquisition and to review the syntactic structures of these phrasal verbs. In doing so, it is designed as a descriptive case study of this phenomenon within its context. In particular, the study examines how these phrasal verbs are arranged, and it presents a full description of these features. The analysis revealed that the syntactic features of phrasal verbs are difficult to comprehend for second language learners due to the various categories related to their structure, especially the separable/inseparable category. To conclude, there are many syntactic criteria based on which PVs can be categorized in terms of structure; this includes transitive/intransitive and separable/inseparable. Also, this paper highlights the distinction between phrasal verbs and prepositional phrasal verbs. Thus, all students should acquire at least an open awareness, enabling them to comprehend the PVs they encounter in spoken and non-spoken texts. Students who want to be proficient language users must be able to produce at least the more general PV combinations in a meaningful manner. Finally, this paper proposes that, as lexical items, phrasal verbs are certainly one of the greatest problematic challenges in language acquisition.